A study of temporomandibular joint morphology and positions among class i, class ii, class iii malocclusion and the effect of petit facemask in class iii malocclusion subjects - Azhar, Mohammed Irfan (2022)
The temporomandibular joint (TMJ) is the most complex synovial joint in the body. TMJ morphology can be affected due to various reasons such as age, sex, increased or decreased muscle activity, the growth pattern of the face, pathological changes, occlusal forces, and changes in the dental occlusion. The effect of these changes can result in remodelling and reconfiguration of the TMJ surfaces. Therefore, careful diagnosis and treatment planning is very essential before the initiation of any orthodontic procedure. The purpose of our study was to evaluate and compare the TMJ morphology of 120 subjects with 40 subjects each in Class I, Class II and Class III malocclusion using pre-treatment lateral cephalometric radiographs (LCRs) and to evaluate and compare the TMJ morphology of 28 subjects with Class III malocclusion treated with petit-FM (Facemask) using pre-and post-treatment LCRs. TMJ evaluation included the measurements of porion location (PL), glenoid fossa, condyle position, condylar height (CH), joint spaces, maxillary base position (MX) and mandibular base position (MD). This was a retrospective cross-sectional study. LCRs were obtained using Planmeca Promax 3D machine (Planmeca Oy, Helsinki, Finland). TMJ morphology measurements were accomplished using the WinCeph cephalometric software version.11 (Rise corporation, Sendai, Japan) for both objectives. Data analysis was performed using SPSS ver.26 software (IBM, SPSS Statistics, Armonk, NY-USA). A one-way ANOVA and Bonferroni post hoc test was done for objective 1, while paired t-test was carried out for objective 2. The comparison of TMJ morphology between Class I, II and III malocclusions showed a significant difference for superior joint space (SJS), posterior joint space (PJS), and MD with (p = 0.00). Correspondingly, the comparison of TMJ morphology between pre-and post-treatment subjects of Class III malocclusion in response to petit-FM therapy revealed significant difference for horizontal positions of the glenoid fossa with (p = 0.00) and (p = 0.03) respectively. Significant difference was observed in hinge axis with (p = 0.00) and (p = 0.04) and all variables of condyle position with (p = 0.00). Lastly, all the joint spaces, MX, and MD showed statistically significant differences with (p = 0.00). In conclusion, the first objective revealed highest SJS and PJS for Class III malocclusion and lowest for Class II malocclusion respectively. There was increase in the length of mandibular base (MD) in Class III subjects which indicate forwardly placed mandible and decrease in Class II subjects which represent backwardly placed mandible. Correspondingly, the second objective demonstrated significant alterations in horizontal position of the glenoid fossa indicating posterior displacement after FM therapy. The hinge axis and condylar head (both superior and posterior condyle) were placed postero-superiorly, while the anterior condyle was placed postero-inferiorly suggesting clockwise rotation of the mandible post treatment. There was an increase in the length of maxillary base which indicate forwardly placed maxilla and decrease in the length of mandibular base which exhibit backwardly placed mandible. Among joint spaces, the anterior joint space (AJS) was found to be larger, and smaller for SJS and PJS post treatment suggesting upward and backward movement of the mandible.